2009
DOI: 10.1177/0040517508095591
|View full text |Cite
|
Sign up to set email alerts
|

High Volume Measurements of Cotton Maturity by a Customized Microscopic System

Abstract: Cotton maturity, the degree of development of the fiber wall relative to its perimeter, is one of the main cotton quality attributes because it directly or indirectly affects most of the other cotton fiber properties. Mature fibers usually possess greater strength and better resilience. The presence of immature fibers may cause excessive fiber damage and waste during processing and may lower yarn strength. Immature fibers have also been recognized as one of the principal causes of the formation of neps, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…While Sirolan Laserscan has been available commercially since the 1990s, other technology has also been available to measure the width of textile fibres, such as the OFDA (BSC Electronics, Australia) (Qi et al 1994), which is based on digital image analysis technology and has now been incorporated into Cottonscope (Rodgers et al 2012). Similarly, Xu et al (2009) described a prototype microscopebased instrument that combined fibre width and translucence measurements to measure fibre maturity. A microscope image determination of ribbon width may well differ from that derived via the laser photometric method and would in turn relate .…”
Section: Models and Fqis Using Alternatives For Micronairementioning
confidence: 99%
“…While Sirolan Laserscan has been available commercially since the 1990s, other technology has also been available to measure the width of textile fibres, such as the OFDA (BSC Electronics, Australia) (Qi et al 1994), which is based on digital image analysis technology and has now been incorporated into Cottonscope (Rodgers et al 2012). Similarly, Xu et al (2009) described a prototype microscopebased instrument that combined fibre width and translucence measurements to measure fibre maturity. A microscope image determination of ribbon width may well differ from that derived via the laser photometric method and would in turn relate .…”
Section: Models and Fqis Using Alternatives For Micronairementioning
confidence: 99%
“…In pursuit of a rapid, but accurate, measurement of cotton fiber maturity that does not have the confounding problems associated with Mic, Xu et al (2009) suggested that fiber maturity may be predicted by the fiber ribbon width (RbWth) and translucency (secondary cell wall thickness). Cotton fibers twist along their longitudinal axes and when depicted in a 2-D image, these twists or convolutions will result in large variations in width of the fiber along the fiber's length.…”
mentioning
confidence: 99%
“…Even though fiber maturity is important to the textile industry, as of yet, a fast, inexpensive, and reliable measurement of maturity does not exist (Hequet et al, 2006). Immature fibers inherently are weaker than more mature fibers and have a tendency to break during mechanical processing, which increases short fiber content (SFC) and in turn increases yarn defects such as neps (entanglements of immature fibers), thick places, thin places and yarn hairiness (Xu et al, 2009). Immature fibers typically do not have enough cellulose to effectively uptake dye, causing white specks in the fabric produced (Damian and Xu, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations